Evaluation of a manual-based training program in changing auxiliary nurse midwives (ANMs) knowledge, attitudes, and skills related to maternal mental health - Vijayalakshmi Poreddi; Sailaxmi Gandhi; Ramachandra; Sundarnag Ganjekar; Geetha Desai; Prabha S. Chandra (Indian Journal of Psychiatry, 2023)
Background: Globally, maternal mental health has been recognized as a priority public health issue. While it is crucial to integrate maternal mental health into mother and child health services, research on strengthening the knowledge and skills of primary healthcare providers on maternal mental health is limited in India. Aim: To evaluate the effectiveness of a manual-based training program in improving auxiliary nurse midwives (ANMs) knowledge, attitudes, and skills related to maternal mental health. Methods: The present study adopted an experimental design among ANMs (N = 110) working at primary health centers, Karnataka, India. The participants were randomly assigned to either experimental group (n = 53) or control group (n = 57). The training program delivered interactive sessions based on a facilitator’s manual developed specifically for ANMs in India. The assessments were done in both groups at baseline, after the intervention, at three months and at six months using self-rated questionnaires and a case vignette. The descriptive and inferential statistics were used to analyze the data. Results: After the training program the mean knowledge, attitudes and skills scores were significantly increased in the experimental group (P < 0.001) and significant differences were found between the mean scores of the groups at 3 months and 6 months follow-up (P < 0.05). Conclusion: The training program was found to have a positive impact in enhancing ANMs’ knowledge, attitudes, and skills related to maternal mental health in India as there is dearth for mental health professionals in primary care settings.